Relevance Of Islamic Banking In Indonesia To The Muamalah System Of The Prophet And The Caliph - Malta Anantyasari; Agus Endro Suwarno; Muh. Nashirudin; Chabibatul Mu'awanah; Nuraini Binti Asri (Journal of Islamic Economic Laws, 2022)
The emergence of Islamic banks in Indonesia today is increasingly mushrooming. This is inseparable from the role of the number of Muslim populations in Indonesia who want an Islamic economic and banking system that is far from usury. The Islamic banking system has been exemplified by the Prophet Muhammad and his companions in the past and this has become the basis or foundation for the establishment of Islamic banks. But in reality in Indonesia, the relevance of the Islamic banking system is less attractive. This research is a descriptive qualitative research, using library research method. The purpose of this study is to examine the practice of Islamic banking as exemplified at the time of the Prophet Muhammad SAW and to see the relevance and development of Islamic banking practices in Indonesia. The conclusion of this study is that the model of banking services, products and activities exemplified by the Prophet is still used in the Islamic banking system in Indonesia, but in fact there are many Islamic bank practices that deviate and are not in accordance with Sharia rules.